बौद्धदर्शन में सम्यक्दृष्टि (Bodhi Path, 2023)
In Buddhism, 'Right View' holds a special significance. It is through the Right View that the path to wellbeing is illuminated. In Buddhism, the Noble Eightfold Path is referred to as the path leading to the cessation of suffering. This path is composed of eight elements, hence the name Noble Eightfold Path. It is also referred to as the Middle Way. The first element in this Noble Eightfold Path is the Right View. The word 'Right' is prefixed to 'View' because views or perspectives can also be false. The term 'Right' helps in warding off false views.